International expansion and home-country resource acquisition: a signaling perspective of emerging-market firms’ internationalization - Du, J; Zhao, EY (Springer, 2023)
Despite growing attention to the role of home countries in studies of emerging-market multinational enterprises (EMNEs), there is limited focus on how international expansion affects EMNEs’ home conditions. Drawing on signaling theory, we propose that EMNEs’ international expansions serve as a signaling mechanism that shapes perceptions of stakeholders in their home countries and thus facilitate their resource acquisition from these stakeholders. The signaling effect is strengthened when EMNEs enter more advanced host countries where higher entry barriers incur higher signaling costs that serve as isolating mechanisms; and when they are located in less developed home markets where information asymmetry is more serious due to weaker institutional arrangements. Furthermore, congruent signals, such as patents, strengthen the main effect by cross-confirming the signaled content, while incongruent signals, such as political connections, weaken it due to ambiguity in interpreting the original signal. Using instrumental variables and a difference-in-differences design to account for potential endogeneity of international expansion, our empirical analysis of Chinese-listed privately owned enterprises from 1999 to 2019 supports our propositions.